(untitled) (Kairaranga, 2021)
The evidence-based anti-bullying programme known as KiVa was introduced into New Zealand in 2015 as an attempt to address high bullying rates. A key component of this programme includes a set of ‘indicated actions’ that are enacted when bullying incidents are reported. This study looked at the implementation of the ‘indicated actions’ component in a small sample of schools in New Zealand over a specific time period. Data collection included individual interviews with KiVa team members from each school. They were asked to provide information about the range and frequency of bullying incidents that were identified using the ‘indicated actions’ procedures, a description of the KiVa procedures in place in the schools, parents and teacher involvement in the KiVa process, and their perceived effects of the programme. Results revealed large variations across schools in the frequency of bullying incidents reported and acted upon. In addition, verbal name-calling was reported by a majority of the schools as being the most prevalent form of bullying. Although all 12 schools reported (and had documentation to show) that they had followed KiVa procedures as outlined in the manual, the use of the screening form was varied and the majority of the KiVa team members perceived the effects of the programme to be positive.